A case of autoimmune pulmonary alveolar proteinosis with severe respiratory failure treated with segmental lung lavage and oral statin therapy. (2022) - Takano, Tomotsugu; Takeda, Keisuke; Nakamura, Satoshi; Akiyama, Genta; Ando, Nobuhisa; Komori, Masashi
Abstract: Pulmonary alveolar proteinosis (PAP) is a diffuse lung disease characterized by the accumulation of alveolar surfactants due to dysfunction of granulocyte-macrophage colony-stimulating factor-dependent cholesterol clearance. Whole-lung lavage is the current standard of care for PAP, but it can lead to the exacerbation of hypoxia. A medication targeting cholesterol homeostasis is a promising therapy for refractory PAP. We present a case of autoimmune PAP with severe hypoxia that was successfully treated with segmental lung lavage (SLL). Following SLL for disease relapse, statin treatment for dyslipidemia was started. After initiating statin treatment, the patient did not require bronchoalveolar lavage for 10 months.